2004
DOI: 10.1111/j.1471-4159.2004.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

The nerve growth factor precursor proNGF exhibits neurotrophic activity but is less active than mature nerve growth factor

Abstract: Nerve growth factor (NGF) promotes neuronal survival and differentiation and stimulates neurite outgrowth. NGF is synthesized as a precursor, proNGF, which undergoes posttranslational processing to generate mature b-NGF. It has been assumed that, in vivo, NGF is largely processed into the mature form and that mature NGF accounts for the biological activity. However, we recently showed that proNGF is abundant in CNS tissues whereas mature NGF is undetectable, suggesting that proNGF has biological functions beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(186 citation statements)
references
References 52 publications
(123 reference statements)
12
171
3
Order By: Relevance
“…However, there is some controversy regarding the prosurvival role of proNGF in the brain. High proNGF concentrations can stimulate PC12 cell survival when the p75NTR/TrkA ratio is low (Fahnestock et al 2004). It was established that the receptors balance, i.e., the relative level of Trk and p75NTR, is a crucial determinant of cell fate during development and that it is required for further modulation of neurite outgrowth/synaptic plasticity in the adult brain (Masoudi et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some controversy regarding the prosurvival role of proNGF in the brain. High proNGF concentrations can stimulate PC12 cell survival when the p75NTR/TrkA ratio is low (Fahnestock et al 2004). It was established that the receptors balance, i.e., the relative level of Trk and p75NTR, is a crucial determinant of cell fate during development and that it is required for further modulation of neurite outgrowth/synaptic plasticity in the adult brain (Masoudi et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that high MW NGF species are abundant in the nervous system and may have their own biological activity. Some have suggested an apoptotic role for proNGF (Lee et al 2001;Beattie et al 2002;Harrington et al 2004;Pedraza et al 2005), though proNGF also has been shown to have neurotrophic activities Reinshagen et al 2000;Fahnestock et al 2004).…”
Section: Function Of Ngf and Nt-3 Protein Speciesmentioning
confidence: 99%
“…Among the NTs, nerve growth factor (NGF) plays a pivotal role in the control of the differentiation and survival of peripheral sympathetic and sensory nerve fibres as well as the functionality of cholinergic neurons (Lindsay et al 1994, Aloe et al 2012. The mature NGF molecule results from the proteolysis of a precursor form (proNGF), which is also bioactive and exerts both pro-apoptotic and neurotrophic effects during development and adult life (Fahnestock et al 2001(Fahnestock et al , 2004. Both forms exert their biological activities upon ligation of the specific tropomyosin kinase receptor A (TRKA), which is a typical tyrosine kinase receptor (Huang & Reichardt 2003), as well as of the low-affinity and non-selective p75 pan-NT receptor (p75NTR).…”
Section: Introductionmentioning
confidence: 99%